Faktor-faktor yang Mempengaruhi Pemanfaatan Program Jampersal di Kabupaten Kaur, Propinsi Bengkulu - Agustina Agustina; Ahmad Farid Umar (STIKes Persada Husada Indonesia, 2014)
According to the results Riskesdas 2010, deliveries by skilled health personnel in poor target groups reached approximately 69.3%. While deliveries conducted by skilled health personnel in health facilities reached 55.4%. According to data from the Ministry of Health, 90 percent of maternal deaths due to childbirth. This is because there are many mothers can not afford that childbirth is not served by health workers and health facilities are good for the cost constrained. Delivery Guarantee Program (Jampersal) was launched in 2011 by Minister Regulation. 631/Menkes/PER/III/2011 on Technical Guidelines for Delivery Guarantee. Participants are pregnant women, birth mothers, postpartum women (up to 42 days postpartum) and newborn (0-28 days) that has not had a labor guarantee.The purpose of this study is to identify the utilization Jampersal program based on predisposing factors, enabling factors, and factor thrusters. in Kaur District. This research is quantitative non-experimental research, the data collected by cross sectional. Research sites in three health centers located in the South region Bintuhan health centers, health centers and clinics Nasal, Linau. The data collected by interviews using a structured questionnaire. Results showed that of the 90 respondents, 48 (53.3%) did not use the program Jampersal and 42 (46.7%) that utilizes Jampersal. This is caused by ignorance of respondents to the service components that free of charge has significant relationship between attitudes to the use Jampersal program (P = 0.026). Attitudes towards midwife rules is the most dominant determinant in the use of program Jampersal with supporters is the midwife's role in disseminating Jampersal and maternal confidence on the ability of midwives.